Validation of a LC-MS/MS method for the quantitative analysis of four antibiotics in pig tissues and plasma to assess the risk of transfer of residues to edible matrices after exposure to cross-contaminated feed. Issue 11 (2nd November 2022) - Santos-Santórum Suárez, Cristina; Sanders, Pascal; Perrin-Guyomard, Agnès; Hurtaud-Pessel, Dominique; Laurentie, Michel; Viel, Alexis; Taillandier, Jean-François; Lagree, Marie-Pierre; Gaugain, Murielle
Abstract: Cross-contamination between medicated and non-medicated feed can occur during production, processing, transport or storage of animal feed. This may lead to the presence of low concentrations of antibiotics in supposedly drug-free feed for food production animals, which potentially could also harm consumers due to residues. In addition, consumption of sub-therapeutic concentrations of antibiotics may increase the risk of emergence of resistant bacteria. In this study, LC-MS/MS methods were developed to quantify four antibiotics (sulfadimethoxine, oxytetracycline, trimethoprim and amoxicillin) in several pig matrices, i.e. plasma, muscle, liver, kidneys and faeces. All methods were validated using the accuracy profile, except for amoxicillin in faeces, for which extraction could not be optimised for low concentrations. These methods were then applied as part of an animal study during which several pigs received contaminated feed at a concentration corresponding to 2% of therapeutic dose, in order to evaluate the risk of the presence of residues in animal faeces and tissues. The results showed that sulfadimethoxine is well absorbed and accumulates in the muscle, kidneys and liver, where concentrations were higher than the maximum residue limits (MRLs) authorised in EU legislation. Conversely, oxytetracycline was mostly found in faeces as its oral absorption is very low. Trimethoprim concentrations were slightly higher than the tolerated MRL in the kidneys, but they were below this level in the other tissues. Finally, amoxicillin concentrations remained below the lower limit of quantification of the methods in all matrices.